2006
DOI: 10.1093/hmg/ddl251
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector expressing retinoic acid receptor β2 promotes recovery of function after corticospinal tract injury in the adult rat spinal cord

Abstract: Spinal cord injury often results in permanent and devastating neurological deficits and disability. This is due to the limited regenerative capacity of neurones in the central nervous system (CNS). We recently demonstrated that a transcription factor retinoic acid receptor beta2 (RARbeta2) promoted axonal regeneration in adult sensory neurones located peripherally. However, it is not known if RARbeta2 can promote axonal regeneration in cortical neurones of the CNS. Here, we demonstrate that delivery of RARbeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 41 publications
3
62
0
1
Order By: Relevance
“…This is mainly associated with the inability of neurons in the CNS to repair or regenerate their axons post-trauma. The use of viral vectors to express neurotrophic 22 or transcriptional factors 23 in the rubrospinal or corticospinal tracts, respectively, in SCI animal models has produced encouraging results. We have demonstrated efficient gene delivery to both corticospinal and rubrospinal tracts in rats using a VSVG pseudotyped NILV vector administered into the cerebral motor cortex or red nucleus, with approximately 20% transfection rate for the corticospinal, and under optimal conditions, more than 40% for the rubrospinal tract, respectively.…”
Section: Efficient Gene Delivery To Adult and Fetal Cnsmentioning
confidence: 99%
“…This is mainly associated with the inability of neurons in the CNS to repair or regenerate their axons post-trauma. The use of viral vectors to express neurotrophic 22 or transcriptional factors 23 in the rubrospinal or corticospinal tracts, respectively, in SCI animal models has produced encouraging results. We have demonstrated efficient gene delivery to both corticospinal and rubrospinal tracts in rats using a VSVG pseudotyped NILV vector administered into the cerebral motor cortex or red nucleus, with approximately 20% transfection rate for the corticospinal, and under optimal conditions, more than 40% for the rubrospinal tract, respectively.…”
Section: Efficient Gene Delivery To Adult and Fetal Cnsmentioning
confidence: 99%
“…We introduced the recombinant lentivirus vectors via the administration of lateral cerebral ventricle injections. Compared to adenovirus, lentivirus has high transfection efficiency in non-dividing cells, a sustained expression potency and minimal impact on normal cellular functions (37)(38)(39). Previous studies have demonstrated the feasibility of the lentivirus-mediated delivery of ERα (26,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although EIAV-based vectors are about 10-fold less efficient in several human cell lines than HIV-1 based vectors (Ikeda et al, 2002), they have demonstrated good efficiency for treatment of neuromuscular pathologies in animal models (Azzouz et al, 2004;Yip et al, 2006). In addition, they are able to transduce human HSCs (Siapati et al, 2005) and are very efficient in vivo.…”
Section: Equine Infectious Anaemia Virus (Eiav)-based Vectorsmentioning
confidence: 99%